Prediction of Cardiovascular Disease in suburban population of 3 municipalities in Nepal - Koju, R; Gurung, R; Pant, P; Humagain, S; Yogol, CM; Koju, A; Manandhar, K; Karmacharya, B; Bedi, TRS (Nepalese Heart Journal, 2013)
Background Cardiovascular disease (CVD) is a major cause of morbidity and mortality throughout the world including Nepal. The assessment of risk factors responsible for CVD can predict 10 year risk of CVD. World Health Organization (WHO) risk assessment chart, specially designed for South East Asia Sub-region D can predict the risk of CVD in Nepal. Method and Materials A total 532 study population from Panauti, Banepa and Dhulikhel were calculated their 10 year risk of CVD using WHO/ISH risk prediction chart on the basis of risk factors: age, gender, smoking status, diabetes, systolic blood pressure and total cholesterol. Result Ten year risk of developing cardiovascular disease is less than 10% among the population less than 50 years, irrespective of gender. 5% of male population had more than 10% chance of developing cardiovascular events in next ten years. One third of 60 – 69 years people had more than 10% chance of developing cardiovascular disease whereas it increased to 50% among 70 years and older group. Conclusion The assessment of risk factors is quite easy and cheap tool to predict the cardiovascular event, which support to practice the good clinical management to prevent the cardiovascular morbidity and mortality. DOI: http://dx.doi.org/10.3126/njh.v8i1.8328 Nepalese Heart Journal Vol.8(1) 2011 pp.3-7